What can I do as a farmer to reduce losses? Willingness to use meteorological information as an exit strategy to deal with meteorological hazards - Valizadeh, Naser; Haji, Latif; Karami, Shobeir; Ahmadi Dehrashid, Atefeh; Jalilian, Sara; Azadi, Hossein (Frontiers in Environmental Science, 2024)
Meteorological information and forecasts are of great importance to reduce agro-meteorological hazards. However, the gap between production and application of these forecasts is one of the most ambiguous issues of crop management at the farmers' level. In this regard, investigating the factors influencing Iranian farmers willingness to use meteorological information and predictions was selected as the main aim of the present study. To this end, an extended version of Theory of Planned Behavior (TPB) was employed and modeled. The results revealed that attitude towards the use of meteorological information and predictions, subjective norms in the use of meteorological information and predictions, perceived behavioral control and self-identity in the use of meteorological information and prediction, and moral norm variables regarding the use of meteorological information and predictions positively and significantly affected willingness to use meteorological information and predictions. These variables could account for 46 % of willingness to use meteorological information and predictions variance. According to the results, it was suggested that by creating multimedia programs, the agricultural community become aware of the benefits and consequences of using meteorological information in their activities. Furthermore, it was recommended that social cooperation and research groups be formed on the use of meteorological information in agricultural activities. This can contribute to examine the various dimensions (strengths, weaknesses, threats, and opportunities) of using meteorological information from a collective perspective. Making a social decision in this regard can have a profound effect on a person's subjective norms and dramatically increase the speed of using meteorological information. The results of this study can help policy-makers and decision-makers in the field of agriculture to design suitable intervention programs for the effective use of meteorological information by farmers. Also, the results of this study help farmers to effectively reduce the impacts of meteorological hazards.